IDENTIFIKASI JENIS DAN ARAH SESAR AKTIF DI WILAYAH SULAWESI SELATAN MENGGUNAKAN METODE HIPOCENTER DAN CENTROID (H-C) - Lorna, Lorna; Rahmaniah, Rahmaniah; Wahyuni, Ayusari (JFT : Jurnal Fisika dan Terapannya, 2019)
This study aims to identify the direction and type of active faults in the region of South Sulawesi by using the hypocenter and Centroid (HC). The data used is secondary data obtained from the hypocenter USGS, IRIS, GEOFON website and the data obtained from BMKG centroid that is processed using the focus mechanism to coordinate limit  LS –  BT. According to the research by the method of HC obtained by the type and direction of the active faults in the region I with the type of normal foult directed N6E/32 south-north , region II with the type of strike-slip fault directed N358E/83  north-south, Region III with the type of oblique fault directed N74E/16  southwest-northeast, Region IV with the type of normal foult directed  N109E/56 northwest- southeast and in the region of V with the type of strike-slip fault directed N332E/50 southeast-northwest.